2020
DOI: 10.1155/2020/1497530
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Common Bean (Phaseolus vulgaris L.) Genotypes for Yield and Related Traits at Areka, Southern Ethiopia

Abstract: Common bean is a source of dietary protein and the second most important legume crop in Africa next to faba bean. In Ethiopia common bean is the most important legume as the source of protein and export commodity. Hence, development of commercial varieties is one of the major tasks to meet increasing demand of the stake holders. To this effect, understanding the genetic variability, heritability and association between grain yield and other agronomic traits is necessary for effective plant breeding program. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Variance components values in Table (6) show that the large portion of genotypic variance for the following characters: plant length, number of branches, pod length, pod width, fresh pod weight, dry pod weight, number of seeds / pod, number of pods / plant, total pods yield / plant, total seeds yield / plant and 100 seeds weight. Moderate values were in traits height of the first pod and number of days to first pod these results were in agreement with those found by Fahad et al, (2014) and Yohannes et al, (2020). They stated that the genotypic (GV) and phenotypic (PV) variability are considered the important criteria in a successful breeding program and understand the genotypic difference of the most important quantity traits.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Variance components values in Table (6) show that the large portion of genotypic variance for the following characters: plant length, number of branches, pod length, pod width, fresh pod weight, dry pod weight, number of seeds / pod, number of pods / plant, total pods yield / plant, total seeds yield / plant and 100 seeds weight. Moderate values were in traits height of the first pod and number of days to first pod these results were in agreement with those found by Fahad et al, (2014) and Yohannes et al, (2020). They stated that the genotypic (GV) and phenotypic (PV) variability are considered the important criteria in a successful breeding program and understand the genotypic difference of the most important quantity traits.…”
Section: Resultssupporting
confidence: 90%
“…Hence, the development of commercial varieties is one of the major tasks to meet the increasing demand of the stakeholders. To this effect, understanding the genetic variability, heritability and association between grain yield and other agronomic traits is necessary for an effective plant breeding program (Yohannes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Yohannes et al. (2020) reported that some of the SMC‐ and SEC‐lines performed better in terms of grain yield and resistance to the major bean diseases at the Areka site in Southern Ethiopia. The common bean lines which were selected for drought tolerance were reportedly resistant to the CBB.…”
Section: Discussionmentioning
confidence: 99%
“…The significant variation observed in cluster number per plant and pod number per plant in the years due to variation in temperature and rainfall (Figure1). The significant variation among the genotypes for green pod number per plant had been reported by many researchers (Akhilesh et al 2013, Muthuramu et al 2015, Yohannes et al 2020. The variation in number of green pod per plant might also be due to differences in inflorescences, pods number per racemeand flower dropping tendency of the genotypes (Khan 2003).…”
Section: Discussionmentioning
confidence: 78%